A Samaritan merchant and his friend, and their friends : practicing life-giving theology - Van Eck, Ernest (Hervormde teologiese studies, 2019)
The Department of New Testament and Related Literature (formerly the Department of New Testament Studies) for the past 100 years has had a proud tradition of practicing life-giving theology. From very early on, several members of the department were critical voices against exclusive and discriminatory narratives of their time. Representing the voices of the disadvantaged, excluded and marginalised people, they critiqued systemic injustices, envisaged inclusive believing communities, advocated an open society with equal opportunities for all and called for social justice. This article shows that the current members of the department are upholding this proud tradition in their research and publications. Common to the current trend in the department is the avoidance of a literal reading of texts by paying attention to the historical and social contexts of texts and using all possible approaches in reading the text from as many angles as possible. This approach has led to new avenues to reread texts with concomitant new interpretations. As an example of this approach, a rereading of the so-called parable of the Samaritan is presented, challenging its dominant and universally accepted interpretation. The article concludes with a statement of intent linked to the vision of the department, that is, to practice and teach life-giving theology that counters individualised and unreflective ways of living by articulating and embracing a theology that leads to a flourishing life for all creation.